DNA Dye Sytox Green in Detection of Bacteriolytic Activity: High Speed, Precision and Sensitivity Demonstrated With Endolysins - Harhala, Marek; Gembara, Katarzyna; Miernikiewicz, Paulina; Owczarek, Barbara; Kaźmierczak, Zuzanna; Majewska, Joanna; Nelson, Daniel C.; Dąbrowska, Krystyna (Frontiers in Microbiology, 2021)
Introduction: Increasing number of deaths from multi-drug resistant bacterial infections has caused both the World Health Organization and the Centers for Disease Control and Prevention to repeatedly call for development of new, non-traditional antibacterial treatments. Antimicrobial enzymes, including those derived from bacteriophages, known as endolysins or enzybiotics, are considered promising solutions among the emerging therapies. These naturally occurring proteins specifically destroy bacterial cell walls (peptidoglycan) and as such, are capable of killing several logs of bacteria within minutes. Some endolysins cause lysis of a wide range of susceptible bacteria, including both Gram-positive and Gram-negative organisms, whereas other endolysins are species- or even strain-specific. To make wide use of endolysins as antibacterial agents, some basic research issues remain to be clarified or addressed. Currently available methods for testing endolysin kinetics are indirect, require large numbers of bacteria, long incubation times and are affected by technical problems or limited reproducibility. Also, available methods are focused more on enzymatic activity rather than killing efficiency which is more relevant from a medical perspective. Results: We show a novel application of a DNA dye, SYTOX Green. It can be applied in comprehensive, real-time and rapid measurement of killing efficiency, lytic activity, and susceptibility of a bacterial population to lytic enzymes. Use of DNA dyes shows improved reaction times, higher sensitivity in low concentrations of bacteria, and independence of bacterial growth. Our data show high precision in lytic activity and enzyme efficiency measurements. This solution opens the way to the development of new, high throughput, precise measurements and tests in variety of conditions, thus unlocking new possibilities in development of novel antimicrobials and analysis of bacterial samples.